Pengaruh token ekonomi untuk meningkatkan kemampuan rawat diri pada individu dengan gangguan skizoafektif - Rullita Aristya Mintarsih (Universitas Muhammadiyah Malang, 2021)
The subject was a 41-year-old woman with a diagnosis of schizoaffective disorder. Subjects showed the symptoms of schizoid that made them less interested in daily activities, less concerned with hygiene and self-care. Assessment methods used are observations, interviews, and psychological tests in the form of WAIS, graphic tests (DAP, BAUM, &HTP), TAT, WWQ and WHODAS questionnaire. Interventions are made to deal with the lack of ability in self-care, using behavior modification therapy with the token economy method. The results showed that Token Economy was effective to improve the subject's ability to care for themselves, they became more motivated to perform basic activities such as self-cleaning.